2018
DOI: 10.1186/s12866-018-1248-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and anti-salmonella activities of lactic acid bacteria isolated from cattle faeces

Abstract: BackgroundNon typhoidal salmonellosis is one of the neglected zoonoses in most African countries. The use of sub-therapeutic doses of antibiotics as animal growth promoter enhances the emergence and dissemination of antimicrobial resistance in bacteria with food animal reservoirs and may also results in antibiotics residue in animal products. One promising alternative to antibiotics in animal feed is Lactic Acid Bacteria (LAB) as probiotics. This study was carried out to determine the anti-salmonella activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 53 publications
8
74
0
4
Order By: Relevance
“…e highest inhibition (100%; p < 0.05) was observed with the combination of the three probiotic strains as in the form of mix 4 (Lactococcus lactis, Lactobacillus plantarum, and Lactobacillus paracasei). In agreement with this study, Adetoye et al [32] have revealed that Lactobacillus salivarius C86 and Lactobacillus amylovorus C94 strains obtained from cattle feces were able to inhibit the growth of Salmonella spp. completely between 8 and 16 hours of coincubation with no recoverable Salmonella spp.…”
Section: Discussionsupporting
confidence: 91%
“…e highest inhibition (100%; p < 0.05) was observed with the combination of the three probiotic strains as in the form of mix 4 (Lactococcus lactis, Lactobacillus plantarum, and Lactobacillus paracasei). In agreement with this study, Adetoye et al [32] have revealed that Lactobacillus salivarius C86 and Lactobacillus amylovorus C94 strains obtained from cattle feces were able to inhibit the growth of Salmonella spp. completely between 8 and 16 hours of coincubation with no recoverable Salmonella spp.…”
Section: Discussionsupporting
confidence: 91%
“…(2019) published that culture supernatants from Lactobacillus ingluviei strain UMNPBX19 and Lactobacillus salivarius strain UMNPBX2 exhibited antimicrobial activity against Salmonella . A study by Adetoye et al. (2018) demonstrated in vitro suppression of Salmonella by intestinal LAB from cattle ( Lactobacillus amylovorus C94 and L. salivarius C86).…”
Section: Resultsmentioning
confidence: 99%
“…infantarius and S . equines in bovine fecal samples, exhibited anti- Salmonella activities [ 59 ]. Our results highlight the potential of using these butyrate-producing bacteria as microbial markers for identifying healthy (high prevalence) or unhealthy (low prevalence) in young ruminants.…”
Section: Discussionmentioning
confidence: 99%